A Tissue Ignored In Cervical Ultrasound: Relationship of Palatine Tonsil Size with Age, Gender, Body Mass Index, and Body Surface Area in the Pediatric Population - Bozbeyoglu, Gulcin; Dogan, Mahmut Bilal (Cerrahpaşa Medical Journal, 2023)
Objective: Evaluation of the palatine tonsils is an important issue both in cases of acute infection and in diseases such as obstructive sleep apnea. This study, it was aimed to determine whether there is a relationship between the palatine tonsil volume and gender, age, body mass index, and body surface area in children by ultrasonography. Methods: Two hundred patients aged 3-15 years were included. The study population was divided into 4 groups, three years apart. Tonsil volume was calculated in mm using the formula “0.52 x length x width x height”. Pearson and Spearman rho tests were used for correlation. Results: Of the study group, 99 (49.5%) were girls. The mean age of the cases was 8.5±3.4. When the patients' ages and right and left palatine volumes were evaluated; a significant but very weak correlation was observed (r:0.167, p=0.018; r:0.161, p=0.023, right and left, respectively). When the palatine volumes of the patients were evaluated according to their BMI and BSA; the result was similar (BMI: r:0.253, p<0.01; r:0.282, p<0.01; BSA: r:0.207, p=0.003; r:0.242, p=0.001). In the PostHoc evaluation, it was observed that statistical significance observed in the 3-6 age group and the 9-12 age group (p=0.028). Conclusions: In this study, it has been observed that tonsil size increases with variables such as age, BMI, and BSA. Determining the normal value of tonsil volume in healthy children will be useful in the diagnosis of diseases with tonsil enlargement.